Penerapan Metode Pembelajaran Flipped Classroom dengan Pendekatan Saintifik Berbantuan Aplikasi WhatsApp dalam Pembelajaran Matematika - Umi Hatanti; Iis Holisin; Endang Suprapti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhhammadiyah kendari, 2022)
The covid-19 pandemic period learning in the schools become online, but at SMA Muhammadiyah 5 Dukun learning is carried out online and face to face. The purpose of the study was to describe process and student learning outcomes after learning using the flipped classroom learning method with a scientific approach assisted by the whatsApp application in learning mathematics. This research was a quantitative study using a One Shot Case Study. The research was conducted in grade 10th of SMA Muhammadiyah 5 Dukun. The data collection methods used were observation, test, and questionnaire. The results of data analysis showed student activity in learning an average of 81.48% including active and moderately active categories. The implementation of learning by teachers with an average of 4.37 was in the good category. Student learning outcomes showed 81.48% of students declared complete KKM. Student responses to the process of implementing learning an average of 72% with positive category.